Is Investment Policy Value-Enhancing through CSR Disclosure? - Jaja Suteja; Annisa Nur Mayasari (Jurnal Keuangan dan Perbankan, 2017)
This study aims to analyze the effect of funding policy, dividend, and investment on firm value and the influence of corporate social responsibility (CSR) disclosure as moderating variable in the relationship between investment policy and firm value. By using purposive sampling methods, the selected sample of this research is 6 property, real estate and construction companies listed on IDX within the period of 2012-2016. Data analysis using the moderated regression analysis. From this study, it has been found that funding policy has no significant effect on firm value, dividend policy has a significant effect on firm value, and investment policy has a significant effect on firm value. The result also significantly showed CSR disclosure proved to be a moderating variable of the relationship between investment policy to firm value. Disclosure of CSR should be considered as a result of the implementation of the decision. The property, real estate, and construction companies should be more aware of the importance of implementing corporate social responsibility to increase corporate value. Disclosure of CSR should be considered as a result of the implementation of the decision.DOI: https://doi.org/10.26905/jkdp.v21i4.1724